Total Quality Management: A Study of Processing the Quality of 99 Brand Coffee Product - Muhammad Zakki (Journal of Islamic Economics Perspectives, 2021)
This study aims to see how the total quality management (TQM) method plays a role in processing 99 coffee products in the Mandiri Mukmin Cooperative. In this study using total qualit management theory and qualitative research. The determination of informants in this study was determined in advance. Data collection was carried out using in-depth interview techniques which were conducted in a structured manner. The data analysis technique starts with doing data reduction, then presenting the data and then drawing conclusions. The data validity technique used the source triangulation technique by comparing the data obtained from each informant. Based on the data analysis carried out, the following conclusions are produced: 1) The implementation of total quality management (TQM) in processing 99 coffee products at the Mukmin Mandiri cooperative is in the packing process which still uses human labor. 2) In controlling the quality of coffee raw materials, the quality of processing is measured from the production process to the application of TQM for coffee products which includes product design, taste, and market service. 3) There are still various kinds of obstacles and problems faced in the TQM process of processing coffee products, namely in the production process the machines used are still not fully manufactured. A space or place to produce at the SME or Home Industry level.